2007
DOI: 10.1080/01411920701582298
|View full text |Cite
|
Sign up to set email alerts
|

Possibilities for pedagogy in further education: harnessing the abundance of literacy

Abstract: In this report, it is argued that the most salient factor in the contemporary communicative landscape is the sheer abundance and diversity of possibilities for literacy, and that the extent and nature of students' communicative resources is a central issue in education. The text outlines the conceptual underpinnings of the Literacies for Learning in Further Education project in a social view of literacy, and the associated research design, methodology and analytical framework. It elaborates on the notion of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 19 publications
(10 reference statements)
1
23
0
Order By: Relevance
“…In Paul's case, many of his everyday literacies are carried out together with other people and it is this networking that allows him to accomplish and enjoy his literacy related activities. This argument is supported by Ivanič, Edwards, Satchwell and Smith (2007), who suggest that students preferred to work collaboratively, writing and/or reading together rather than independently. Collaboration is an aspect of literacy practices in many domains of life, particularly in the workplace but also, as we have seen in the case of Paul, in the home too.…”
Section: I T E R a C Y And N U M E R A C Y S T U D I E Ssupporting
confidence: 61%
“…In Paul's case, many of his everyday literacies are carried out together with other people and it is this networking that allows him to accomplish and enjoy his literacy related activities. This argument is supported by Ivanič, Edwards, Satchwell and Smith (2007), who suggest that students preferred to work collaboratively, writing and/or reading together rather than independently. Collaboration is an aspect of literacy practices in many domains of life, particularly in the workplace but also, as we have seen in the case of Paul, in the home too.…”
Section: I T E R a C Y And N U M E R A C Y S T U D I E Ssupporting
confidence: 61%
“…project (Ivanic et al, 2007;. The three year study of the literacies associated with learning across a range of subjects and levels in four colleges in Scotland and England indicated that the diversity of literacies associated with the study of lower level and vocational courses was greater than that associated with the study of more conventional academic subjects.…”
Section: This Latter View Was Challenged By the Literacies For Learnimentioning
confidence: 99%
“…Becoming academically literate involves not only being aware of the rules and expectations of the academic community, but also being able and willing to follow them. It is well documented that many students, particularly those at the beginning of higher education, find the rules of the academic community daunting and challenging especially if they have had limited prior exposure to academic Discourse (Gourlay, 2009;Ivanič, Edwards, Satchwell, & Smith, 2007;Lea & Street, 1998).…”
Section: Academic Literaciesmentioning
confidence: 99%